2019
DOI: 10.18632/oncotarget.27148
|View full text |Cite
|
Sign up to set email alerts
|

Anti-VEGFR2 therapy delays growth of preclinical pediatric tumor models and enhances anti-tumor activity of chemotherapy

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) is an attractive therapeutic target in solid malignancies due to its central role in tumor angiogenesis. Ramucirumab (Cyramza®, LY3009806) is a human monoclonal antibody specific for VEGFR2 approved for several adult indications and currently in a phase 1 clinical trial for pediatric patients with solid tumors (NCT02564198). Here, we evaluated ramucirumab in vitro and the anti-murine VEGFR2 antibody DC101 in vivo with or without chemotherapy across a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Ramucirumab inhibits cord formation by neuroblastoma cells and its analog DC101 delays or regresses xenograft growth, decreases vasculature, and increases chemotherapy effectiveness [ 105 , 122 ]. Pazopanib does not reduce cell viability as a single agent, but it does when combine with topotecan [ 123 ].…”
Section: Antiangiogenics and Neuroblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…Ramucirumab inhibits cord formation by neuroblastoma cells and its analog DC101 delays or regresses xenograft growth, decreases vasculature, and increases chemotherapy effectiveness [ 105 , 122 ]. Pazopanib does not reduce cell viability as a single agent, but it does when combine with topotecan [ 123 ].…”
Section: Antiangiogenics and Neuroblastomamentioning
confidence: 99%
“…The results obtained with ramucirumab in preclinical models are not very promising either. Ramucirumab inhibits the cord formation of osteosarcoma cells in vitro, but its analogue DC101 has limited efficacy in xenografts as single agent or combined with chemotherapy [ 122 ].…”
Section: Antiangiogenics and Bone Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the highly specific VEGFR-2 inhibitor, apatinib, was associated with direct anti-tumoral activity through VEGFR2/STAT3/BCL2 signaling [121,128]. Targeting VEGFR-2 with the monoclonal antibody ramucirumab was also shown to exert anti-angiogenic activity in vitro [129]. Surprisingly, injection of anti-mouse Vegfr-2 antibody in preclinical OS pediatric cancer models did not affect tumor growth, even when combined with cytotoxic chemotherapy using doxorubucin, suggesting that targeting both tumor and vascular microenvironment is mandatory in OS, even if it is difficult to achieve efficiently.…”
Section: Targeting the Vascular Microenvironment With Anti-angiogenicmentioning
confidence: 99%
“…This bone cancer is known as a highly necrotic tumor even at diagnosis, where this histological feature is frequently observed on biopsies. This necrosis might be the consequence of the excessive and rapid growth of cancer cells, which are proficient in creating a hypoxic microenvironment [ 6 , 7 ] and an abnormal neoangiogenesis [ 8 , 9 ]. Besides finding tumor necrosis at biopsy, OTS is also characterized by necrotic rate assessment on surgical tumor resection after a neoadjuvant multichemotherapy approach.…”
Section: Introductionmentioning
confidence: 99%